“We did it just for fun”: Amateur Filmmaking at the Lakehead, 1929-1930 - Beaulieu, Michel (Ontario History, 2007)
This article chronicles the brief existence of The Port Arthur Amateur Cinema Society and its attempts to produce three feature-length films, including Canada’s first amateur feature-length film, A Race for Ties, in 1929. I argue that the existence and success of such a society in the then remote city of Port Arthur, Ontario, owes as much to the dedication of two people – Dorothea Mitchell and Fred Cooper – as it does to the growing culture of consumerism that was a hallmark of the early twentieth century.